B-cell Translocation Gene 2 (BTG2) Stimulates Cellular Antioxidant Defenses through the Antioxidant Transcription Factor NFE2L2 in Human Mammary Epithelial Cells - Karve, Tejaswita M. (American Society for Biochemistry and Molecular Biology, 2012)
The B-cell translocation gene 2, BTG2, a member of the BTG/TOB (B-cell translocation gene/transducers of ErbB2) gene family, has been implicated in cell cycle regulation, normal development, and possibly tumor suppression. Previously, it was shown that BTG2 expression is lost or down-regulated in human breast cancers. We now report that BTG2 protects human mammary epithelial cells from oxidative stress due to hydrogen peroxide and other oxidants. BTG2 protection against oxidative stress is BRCA1-independent but requires the antioxidant transcription factor NFE2L2 and is associated with up-regulation of the expression of antioxidant enzymes, including catalase and superoxide dismutases 1 and 2. BTG2 stimulation of antioxidant gene expression is also NFE2L2-dependent. We further demonstrate that BTG2 is a binding partner for NFE2L2 and increases its transcriptional activity. In addition, BTG2 is detectable at the antioxidant response element (ARE) of several NFE2L2-responsive genes. Finally, we show that the ability of BTG2 to associate with NFE2L2, to protect cells against oxidative stress, and to stimulate antioxidant gene expression requires box B, a short highly conserved amino acid motif characteristic of BTG2/TOB family proteins, but does not require boxes A or C. These findings suggest a novel role for BTG2 as a co-activator for NFE2L2 in up-regulating cellular antioxidant defenses.